Partisipasi Masyarakat pada Daya Tarik Wisata Pantai Maimol di Kabupaten Alor. - Nugraha, Yudha Eka; Meko, Pasifikus Mala; Blegur, Yerry B. G. (Jurnal Ilmu Kesejahteraan Sosial, 2020)
According to Indonesian tourism policy in UU 10 year 2009, tourism will increase community welfare towards community participation. This research aims to identify community participation in tourism activity of Maimol beach using three main concepts namely: factors, forms and levels of participation. The method used was descriptive qualitative by conducting observations and direct interviews with predetermined informants such as the Government, the beach management, the community and tourists, as well as collecting research evidence in the form of image documentation. The results showed that the community around the Maimol beach had participated by working together for every decision was made, opened stalls selling various foods such as corn, peanuts, coconut and grilled fish, as well as participating in cleaning the beach area. Moreover, the level of participation is remaining low because it is constrained by the lack of cooperation between the government and Maimol Beach Management..